The provision of higher education in regional areas: an integrative review of the literature. Issue 3 (4th May 2017) - Wirihana, Lisa; Welch, Anthony; Williamson, Moira; Christensen, Martin; Bakon, Shannon; Craft, Judy
ABSTRACT: There is a great deal of literature surrounding the needs of regional Australia. This integrative review of the literature focuses on the experience of nursing academics teaching on a satellite campus, many of which are located in regional Australia. Four themes were identified: (1) challenges specific to regional satellite campuses, (2) student characteristics, (3) student experiences and (4) the academics' experiences. These themes identified not only significant benefits but also considerable challenges to the provision of higher education on regional university campuses. The experience of nursing academics and indeed their students is remarkably different from the experience of their metropolitan counterparts, and therefore the local context needs to be considered in regional education provision. Australian regional nursing academics need to be multi-skilled to address the workload and social inequity in support service provision.